The Impact of Holder Pasteurization on Macronutrients, Vitamins, Minerals, and Bioactive Factors in Human Milk Processed in a Milk Bank Setting - Autumn Davis; Sheridan Lee; Daniela Hampel; Setareh Shahab-Ferdows; Lindsay H Allen; Lars Bode; Kimberly Mansen; Kiersten Israel-Ballard; Maryanne T Perrin (Current Developments in Nutrition)
Background: Donor human milk is recommended for the nutritionally vulnerable preterm infant; however, there is conflicting or limited information on how the pasteurization techniques used on donor milk influence its nutritional and immune properties. Additionally, prior pasteurization studies were often not reflective of the volume and equipment used in milk bank settings, limiting their generalizability. Objectives: Evaluate the impact of Holder pasteurization—performed in a milk bank setting and using standardized preanalytical handling techniques—on the energy, macronutrients, human milk oligosaccharides, vitamins, minerals, and antimicrobial protein content of human milk. Methods: Fifty matched pairs of raw and Holder-pasteurized milk samples that were collected and pasteurized in a milk bank setting provided the sampling frame. Each pair was from a unique, approved milk bank donor to the Mothers’ Milk Bank of North Texas. A total of 29 nutrients and bioactive factors were assessed using a variety of analytical methods. Results: There was evidence of minimal losses (<15%) in copper, calcium, thiamine, and nonprotein nitrogen, moderate losses in immunoglobin A concentrations (35%), and extensive losses in lactoferrin (>80%). Conclusions: Holder pasteurization has minimal to no impact on energy and essential nutrients in donor milk, including macronutrients, human milk oligosaccharides, B vitamins, and minerals. Moderate to extensive loss of antimicrobial proteins warrants research into alternative preservation techniques.